Retrospective comparative evaluation of airway management with different techniques of fiberoptic intubation in patients undergoing surgery for temporomandibular joint ankylosis - Kumar Saini, Varun; Saini, Priyanka; Soni, Priyanka; Khandelwal, Manish (Journal of Applied Pharmaceutical Research, 2024)
Background: Temporomandibular fusion has devastating effects on the growth and development of an individual's jaws. Thus, surgical modality is seen as a last resort to its correction. Surgical management of temporomandibular ankylosis cases presents significant challenges to an anesthetist in maintaining airway patency. Thus, this retrospective study evaluated the techniques for combating airway management challenges, emphasizing developing an institutional protocol that effectively minimizes errors. Methods: This retrospective study was conducted in the RUHS College of Dental Sciences and attached to the RUHS College of Medical Sciences, Jaipur, Rajasthan, India, for a period of three years. The records of 94 patients who had undergone surgical correction of TMJ ankylosis and were intubated with fiberoptic intubation were compiled. The cases were divided into groups, Group General anesthesia (GA) and Group Regional anesthesia (RA), and analyzed for demographics, successful intubation, and complications. Results: In Group GA, 98 % of cases were successfully intubated. Patient movements were 0 in Group GA and 25% in Group RA. Coughing was present in 1.61% of cases of group GA and 98.38% of Group RA. Epistaxis occurred in 35% of cases, and 29% of cases suffered from sore throat after extubation in Group GA. Conclusion: The anesthetist dilemma of intubating awake or anesthetized always exists. However, a careful preoperative evaluation and assessment of the patient for mask ventilation helps in the successful anesthetic management of temporomandibular joint ankylosis cases. For the anticipated difficult airway awake, fiberoptic intubation is still the ‘gold standard’ technique.